2021
DOI: 10.1177/20578911211000854
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to digital appeals to participate in collective action posted by influentials on protest information sharing: Evidence from Japan and South Korea

Abstract: Contemporary collective action theories put large horizontal digitally connected networks at the center of mass political action. They posit that information sharing among ordinary social media users makes possible new forms of rapid mass political action. However, recent research has shown that influential individuals can play a number of key roles in facilitating networked political action in seemingly leaderless movements. Still, the role of influential individuals in stimulating protest information sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The effects of direct mobilization strategies have been addressed in protest research suggesting that direct appeals, for instance, can indeed mobilize people to protest participation offline (Rone, 2022). Recent research has shown that digital appeals motivate people to engage in digital protest actions (Jenkins, 2020).…”
Section: Effects Of Mobilization Strategiesmentioning
confidence: 99%
“…The effects of direct mobilization strategies have been addressed in protest research suggesting that direct appeals, for instance, can indeed mobilize people to protest participation offline (Rone, 2022). Recent research has shown that digital appeals motivate people to engage in digital protest actions (Jenkins, 2020).…”
Section: Effects Of Mobilization Strategiesmentioning
confidence: 99%